Vertical the city from satellites to bunkers - Graham, Stephen 1965- (Verso, 2016)
"From the penthouse to the sewers...the political geography of the vertical city Vertical is a brilliant re-imagining of the world we live in. Today we live in a world that can no longer be read as a two-dimensional map. In Vertical Stephen Graham rewrites the city at every level, calling for a a new understanding of our surroundings that takes into account above and below: why Dubai has been built to be seen from GoogleEarth; how the superrich in Sao Paulo live their penthouse lives far from the street; why London billionaires build vast subterranean basements rather than move house. Vertical will make you look at the city anew: from the viewfinders of drones, satellites, from the top of skyscrapers, at street-level and from underground bunkers: this is a new politics of space and geography"...
Includes bibliographical references and index
Keywords: SOCIAL SCIENCE / Sociology / Urban; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development; ARCHITECTURE / General; Gesellschaft; Stadt; Cities and towns -- Growth; Land use, Urban; Space (Architecture) -- Social aspects